Changes of Blood Pressure in Hypertension Patients Through Isometric Handgrip Exercise - Andri, Juli; Padila, Padila; Sartika, Andry; Andrianto, Muhammad Bagus; J, Harsismanto (JOSING: Journal of Nursing and Health, 2021)
This study aims to identify the effect of isometric handgrip exercise on changes in blood pressure in people with hypertension. Quasi experimental research design with two group pretest postest research design on 16 respondents. The results showed that there were changes in systolic and diastolic blood pressure after the isometric handgrip exercise intervention (t = 8,279, p = 0,000), (t = 6,154, p = 0,000). In conclusion, there was a difference between the decrease in systolic and diastolic blood pressure in the isometric handgrip exercise intervention group. Keywords: Blood Pressure, Hypertension, Isometric Handgrip Exercise